READING THE VALUES OF RELIGIOSITY AND HUMANITY CHARACTERS IN MODERN INDONESIAN LITERATURE IN LITERATURE LEARNING - Suroso Suroso; Hartono Hartono; Wijang Iswara Mukti; Ratna Intan Sari (TELL - US JOURNAL, 2026)
This article examines the role of religiosity and humanitarian values in modern Indonesian literature and their implications for literature learning in higher education. Unlike philosophy or history, literature presents reality through imaginative expression while adhering to principles of plausibility, integrity, novelty, and aesthetic value, making it a strategic medium for conveying moral and spiritual messages. Using a descriptive-qualitative method with content analysis, this study analyzes selected literary works, including Sang Pencerah by Akhmal Nasery Basral, Negeri 5 Menara by A. Fuadi, Laskar Pelangi by Andrea Hirata, Kubah by Ahmad Tohari, Family of Permana by Ramadhan K.H., as well as short stories by A.A. Navis, Umar Kayam, and Nugroho Notosusanto. The findings indicate that these works contain strong dimensions of religiosity, such as monotheism, worship, and faith, alongside humanitarian values including friendship, empathy, devotion, and social awareness, which are embedded in characters, settings, and narrative conflicts. These values can be utilized as effective media for character education in higher education, particularly in fostering tolerance, responsibility, and respect for others. The study offers novelty by integrating religious and humanitarian values into character-based literature learning strategies, positioning literature not only as an aesthetic form but also as a relevant instrument of moral and humanitarian education in responding to globalization and the moral challenges faced by younger generations.